Operating systems - Palmer, Michael; Walters, Michael (Singapore : Cengage Learning Asia Pte Ltd, 2012)
This text presents information that every technician needs in order to successfully support the desktop operating systems in use in the business world today.
Operating System Theory -- Popular Operating Systems -- Operating System Hardware Components -- File Systems -- Installing And Upgrading Operating Systems -- Configuring Input And Output Devices -- Using And Configuring Storage Devices -- Modems And Other Communications Devices -- Network Connectivity -- Resource Sharing Over A Network -- Standard Operating And Maintenance Procedures.
Includes index.
Keywords: OPERATING SYSTEMS (COMPUTERS)